(untitled) - Charles Conrad (New York, 1998)
This book is divided inti two units. Unit I introduces the theoretical framework that unifies the book and develops the concept of strategies of organizing in detail. It concludes with an extended discussion of communicatio technologies which treats them not as a separate topic, but as processes that modify and expand the strategies of organizing available to members of organizations. Unit II examines a number of situations that employees encouter in contemporary organizations and discusses the communicative strategies that they might use to strategically manage those situations.
Keywords: organizational behavior